Theaflavin-regulated Imd condensates control Drosophila intestinal homeostasis and aging - Qingshuang Cai; Shanming Ji; Mengwan Li; Sen Zheng; Xiuhong Zhou; Huimin Guo; Siyu Deng; Junyan Zhu; Daxiang Li; Zhongwen Xie (2021)
Black tea is the most widely consumed tea drink in the world and has consistently been reported to possess anti-aging benefits. However, whether theaflavins, one type of the characteristic phytochemicals in black tea extracts, are involved in regulating aging and lifespan in consumers remains largely unknown. In this study, we show that theaflavins play a beneficial role in preventing age-onset intestinal leakage and dysbiosis, thus delaying aging in Drosophila. Mechanistically, theaflavins regulate the condensate assembly of Imd to negatively govern the overactivation of Imd signals in fruit fly intestines. In addition, theaflavins prevent DSS-induced colitis in mice, suggesting theaflavins play a role in modulating intestinal integrity. Overall, our study reveals a molecular mechanism by which theaflavins regulate gut homeostasis likely through controlling Imd coalescence.